Images in Clinical Medicine Vol 26(2), 2025 - Habibullah, Mohammad; Atiqullah, Syed; Parvez, Sumaiya; Ali, Syed Mohammad Monowar; Khan, Morshedul Alam; Hossain, Md Asif (Journal of Medicine, 2025)
A 15-year-old girl presented with progressive fatigue lasting 6 months, multiple purpuric spots on both lower limbs, and bleeding gums over the past few days, leading to her admission at Dhaka Medical College Hospital. She reported repeated upper respiratory tract infections, low-grade fever, and increasing pallor in recent months. During her previous admission, she was diagnosed with pancytopenia of unknown cause, with normal bone marrow cellularity. She received two units of whole blood transfusion. Physical examination showed a severely anemic girl of short stature (4'6", below the 5th percentile), frontal bossing, polydactyly (six digits on the left hand), Café au lait spots, a hypopigmented macule on the back, non-palpable purpuric spots and ecchymoses on the limbs, gum bleeding, and ecchymoses on the tongue. There was no organomegaly or lymphadenopathy. She was subsequently diagnosed with aplastic anemia due to Fanconi’s anemia. J MEDICINE 2025; 26(2): 171-172